Genetic detection and identification of the candidate resistance gene for a major QTL resistant to Puccinia polysora in maize. (September 2022) - Tian, Zhiqiang; Du, Wenjie; Li, Zheng; Deng, Ce; Lv, Meng; Li, Xueying; Zhao, Xiaodi; Hao, Junjie; Han, Liping; Li, Zhimin; Ding, Junqiang
Abstract: Southern corn rust (SCR) is a major foliar disease in maize. Identification the major QTL and candidate resistance gene is prerequisite in maize resistance breeding programs. To identify major resistance loci/gene(s) resistant to SCR, a recombinant inbred line (RIL) population derived from a cross between 975 and 12 (resistant) and Lx9801 (susceptible) was analyzed. In total four QTLs were identified, which were located on chromosomes 5, 9 and 10, respectively. Among them, a major QTL on chromosome 10 ( qSCR3 ), were detected in all the environments, which can explain 70.3–78.4% of the total phenotypic variation. Fine-mapping of qSCR3 delimited the QTL to an interval of ∼225 Kb. Using transcripts assembly of the 975–12 and a susceptible mutant (975-12S), an NLR gene, Zm00025ab420970, was identified as the candidate gene for qSCR3, which is a new allele/gene resistant to SCR in maize. Since qSCR3 is a major QTL resistant to SCR, it can be used as a desirable resistance source in maize resistance breeding programs. Highlights: One major QTL ( qSCR3 ) on chromosome10 was detected and candidate gene for the QTL was identified. Fine-mapping of qSCR3 delimited the QTL to an interval of ∼225 Kb. Which make qSCR3 to be a desirable source in maize resistance breeding programs.